Geotechnical properties of two deep-sea marine soils from the Labrador Sea - Morin, Pierre; Dawe, C. Roy (Canadian Geotechnical Journal, 1987)
Cores from two deep-sea sites from the Labrador Sea have been extensively studied using various analyses. X-ray techniques provided a continuous profile of bulk densities and an accurate description of the bedding. The soil structure was analyzed by scanning electron microscopy. Detailed identification, laboratory shear strength, and compressibility tests have been used to determine the geotechnical properties of the soils, both in their intact and remolded states. Geological data and fabric observations are compared with geotechnical properties in order to explain the observed overconsolidation of the surficial sediments. Characterization of the seabed materials is further improved by using existing empirical correlations with soils of onshore and offshore origin. Key words: marine sediments, deep-sea investigation, overconsolidation, laboratory testing, offshore.